The Influence of Debt to Equity Ratio (DER) and Return on Assets (ROA) on Share Prices in Property & Real Estate Sector Companies Listed on the Indonesian Stock Exchange for the 2013-2017 Period - Dewi, Puput Saputri; Sapruwan, Muhammad (Lentera Ilmu Nusantara, 2024)
In The purpose of this research was to determine the effect of debt to equity ratio and return on assets on stock price. The samples used were 17 property & real estate sector companies listed on the Indonesia Stock Exchange in 2013-2017. The sample technique used was purposive sampling. This study uses secondary data in the form of published annual reports. The methods used in this study are descriptive statistical analysis, classical assumption test, multiple linear regression, t test, F test and coefficient of determination test. The data was processed using SPSS Version 23. Based on the results of the study it is known that partially the debt to equity ratio has no effect on stock price and return on asset effects stock price, while simultaneously to equity ratio and return on asset effects stock price..